Churn-Resilient Replication Strategy for Peer-to-Peer Distributed Hash-Tables - Legtchenko, Sergey; Monnet, Sébastien; Thomas, Gael (Stabilization, Safety, and Security of Distributed Systems (SSS'09), 2009)
Abstract. DHT-based P2P systems provide a fault-tolerant and scalable mean to store data blocks in a fully distributed way. Unfortunately, recent studies have shown that if connection/disconnection frequency is too high, data blocks may be lost. This is true for most current DHT-based system’s implementations. To avoid this problem, it is necessary to build really efficient replication and maintenance mechanisms. In this paper, we study the effect of churn on an existing DHT-based P2P system such as DHash or PAST. We then propose solutions to enhance churn tolerance and evaluate them through discrete event simulations.